Co-sputtered MoRe thin films for carbon nanotube growth-compatible superconducting coplanar resonators. (22nd February 2016) - Götz, K J G; Blien, S; Stiller, P L; Vavra, O; Mayer, T; Huber, T; Meier, T N G; Kronseder, M; Strunk, Ch; Hüttel, A K
Abstract: Molybdenum rhenium alloy thin films can exhibit superconductivity up to critical temperatures of . At the same time, the films are highly stable in the high-temperature methane/hydrogen atmosphere typically required to grow single wall carbon nanotubes. We characterize molybdenum rhenium alloy films deposited via simultaneous sputtering from two sources, with respect to their composition as function of sputter parameters and their electronic dc as well as GHz properties at low temperature. Specific emphasis is placed on the effect of the carbon nanotube growth conditions on the film. Superconducting coplanar waveguide resonators are defined lithographically; we demonstrate that the resonators remain functional when undergoing nanotube growth conditions, and characterize their properties as function of temperature. This paves the way for ultra-clean nanotube devices grown in situ onto superconducting coplanar waveguide circuit elements.